2021
DOI: 10.20944/preprints202106.0500.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lemongrass Essential Oil Components with Antimicrobial and Anticancer Activities

Abstract: The prominent cultivation of lemongrass relies on the pharmacological incentives of its essential oil. The lemongrass essential oil (LEO) has a significant amount of citral (mixture of geranial and neral), isoneral, isogeranial, geraniol, geranyl acetate, citronellal, citronellol, germacrene-D, and elemol in addition to numerous other bioactive compounds. These components confer various medicinal activities to LEO including antifungal, antibacterial, antiviral, anticancer, and antioxidant properties. These att… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 130 publications
0
1
0
Order By: Relevance
“…verum contains aroma benzylisoquinoline, benzyl benzoate, terpenoids, cinnamaldehyde, linalool, cinnamyl acetate, eugenol, transcinnamyl, proanthocyanidins and camphor, which elicits antimicrobial, antidiabetic and anti-ulcers properties [13,114]. Cymbopogon citratus was investigated and found to possess a scent citral, limonene, quercetin, kaempferol and geraniol, which are utilized as ant carcinogenic and had ability to kill bacteria [31,115]. Back to Ipomoea cairica, it has anticancer, antidiabetic, antihypertension, ant jaundice, ant HIV transcriptase and antimicrobial activities was elevated by its coumarin derivatives, lignans, cairicoside, scopoletin, glycoresins, arctigenin, convolvine, cyanogenic glycoside, matairesinol, trachelogenin, caempferol and indole alkaloid [38,116,117] Ursolic acid, butulic acid, jacaranone, gallic, quercetin, betulinic acid, maslinic acid, caempferol, iridoids, quinones, phenylpropanoids, phytol, piperidinone, N-[4bromo-n-butyl], hexadecanol, caryophyllene, caffeic acids and coniferol were reported by Kaur et al [118], Naz et al [40] and Mostafa et al [119], to be found in Jacaranda mimosifolia and are accountable for the antibacterial, antiprotozoal, antidiabetic and antitumor.…”
Section: Cinamomummentioning
confidence: 99%
“…verum contains aroma benzylisoquinoline, benzyl benzoate, terpenoids, cinnamaldehyde, linalool, cinnamyl acetate, eugenol, transcinnamyl, proanthocyanidins and camphor, which elicits antimicrobial, antidiabetic and anti-ulcers properties [13,114]. Cymbopogon citratus was investigated and found to possess a scent citral, limonene, quercetin, kaempferol and geraniol, which are utilized as ant carcinogenic and had ability to kill bacteria [31,115]. Back to Ipomoea cairica, it has anticancer, antidiabetic, antihypertension, ant jaundice, ant HIV transcriptase and antimicrobial activities was elevated by its coumarin derivatives, lignans, cairicoside, scopoletin, glycoresins, arctigenin, convolvine, cyanogenic glycoside, matairesinol, trachelogenin, caempferol and indole alkaloid [38,116,117] Ursolic acid, butulic acid, jacaranone, gallic, quercetin, betulinic acid, maslinic acid, caempferol, iridoids, quinones, phenylpropanoids, phytol, piperidinone, N-[4bromo-n-butyl], hexadecanol, caryophyllene, caffeic acids and coniferol were reported by Kaur et al [118], Naz et al [40] and Mostafa et al [119], to be found in Jacaranda mimosifolia and are accountable for the antibacterial, antiprotozoal, antidiabetic and antitumor.…”
Section: Cinamomummentioning
confidence: 99%
“…From Table 1, the main components of Java lemongrass oil are geranial (30.06%), zcitral (25.88%), eugenol (12.88%), and betamyrcene (12.84%). These components are the key components responsible for the oil's antibacterial characteristics (Jafari et al, 2012;Mukarram et al, 2021;Onawunmi et al, 1984).…”
Section: Properties Of Lemongrass Oilmentioning
confidence: 99%
“…Lemongrass oil has been reported to have antimicrobial properties (Jafari et al, 2012;Mukarram et al, 2021), antifungal activities (Mukarram et al, 2021;Tzortzakis and Economakis, 2007), anti-angiogenic agent (Piaru et al, 2012), and antioxidant properties (Mukarram et al, 2021). The Cymbopogon citratus oil was also tested for anti-cancer activity (Mukarram et al, 2021;Piaru et al, 2012;Trang et al, 2020). The active components of lemongrass can be grouped into 3, citral-a (geraniol), citral-b (neral), and myrcene.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9] At present, many reports are being published on geraniol and citral, demonstrating their potential anticancer effects and their scope in alternative cancer therapy. 10 With the rapidly increasing importance of monoterpenes in the production of human fragrances and tastes, demand for new monoterpenes on the market will continue to rise. At present, most of the flavouring products available in the market are produced by chemical synthesis.…”
Section: Introductionmentioning
confidence: 99%